Engaging Vocational Students with Construct-Based Games: A Study on Software and Game Development Interest - Mureno, Althaf Dhava; Musta'amal, Aede Hatib (Universitas Negeri Malang, 2023)
The transformation of learning in the era of technological disruption and pandemic has caused face-to-face classroom learning to transform into online learning or blended learning. Basic Software and Game Programming lessons have skills in identifying and applying how to develop software and games properly. In the school environment there are still many students experiencing difficulties in fostering interest in learning, this is because the process of honing their skills in the form of media that is less interesting. The focus of this research is to develop a website-based educational game learning media for Basic Software and Game subjects with the scope of Structured Programming elements that can increase students' interest in learning. The development methodology applied in this research is the MDLC model. The MDLC development model has 6 research components, including: (1) Concept (2) Design (3) Material Collecting, (4) Assembly, (5) Testing and (6) Distribution (Riyanto & Singgih, 2015). This research will use a questionnaire as a research instrument, and the selection of analysis techniques in this development uses quantitative analysis.